The representation of the Ghost in contemporary South African novels by black writers - Dladla, Asakhe (Department of English Language and Literature, 2025)
The thesis reads the representations of the ghost in South African novels by black writers. The reading is specific to the context of the ghosts haunting South Africa. I ask: how has the ghost been represented by black South African novelists, and what does it signal/tell? The thesis finds that there is a relative paucity of critical studies on depictions of ghosts haunting South African novels as written by black writers. Depictions of ghosts by black South African novelists proliferated after 2000. Black South African novelists writing ghosts emerged as a proliferating current of novel writing after 2000. I account for the representational strategies, functions, effects, and meanings the novelists use to produce the vitality of the depictions of their ghosts to the novel's work. For this study, I read the uses of the ghost in Yvette Christiansë's Unconfessed (2006), Vera the Ghost in Kagiso Lesego Molope's This Book Betrays My Brother (2012), and Senami Tladi's ghost in Niq Mhlongo's Way Back Home (2013). It is in the ghost that I sustain a hermeneutic interest in the novels cited. It is an interest in what the ghost is doing to thinking, reading, and interpreting the work of the black novelist's text that it haunts. There is a sustained interest in the ghost commonality across the works, the ghost representations across the novel texts. These are corresponding efforts: to sustain the hermeneutic interest in the ghost, the interest in interpreting the particularity of the work through the depiction of the ghost that haunts it and sustaining the interest in the ghost commonality haunting across the novel works. The interpretative implications of the represented ghosts of the dead pulled me to say: I am watching the ghosts of the South African novel.